Investigating the impact of Instructional Consultation on the practice of Teaching Assistants - Gill, Randeep Kaur (2016)
A growing body of research investigating the role and impact of the Teaching Assistant (TA) has highlighted the possible detrimental impact that the quality of TA support may have on the academic outcomes of students (Blatchford, Russell, & Webster, 2011). Despite this, the literature offers few evidence-based, systematic suggestions of how the practice of TAs can be developed.